Spinel material, proton ceramic electrochemical cell and preparation method
A Cs-doped spinel-based composite material addresses the low-temperature performance issues in PCECs, enhancing electrocatalytic activity and stability for oxygen and ethane reactions, facilitating efficient power generation and ethylene production.
Patent Information
- Application Number
- CN202411116225.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-20
AI Technical Summary
Existing proton ceramic electrochemical cells (PCECs) face challenges in electrocatalytic performance due to slow electrode reaction kinetics at low temperatures, particularly for oxygen reduction, oxygen evolution, and non-oxidative ethane dehydrogenation, limiting their efficiency and stability.
Development of a Cs-doped spinel-based composite material, Mn0.9Cs0.1Co2O4-δ, and Co3O4, optimized through precise control of preparation conditions, enhances electrocatalytic activity and stability for oxygen reduction, evolution, and ethane dehydrogenation reactions.
The composite spinel material exhibits high electrocatalytic activity and stability, enabling efficient power generation and ethylene production in PCECs, with reduced polarization impedance and improved reaction kinetics.
Smart Images

Figure CN119160946A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton ceramic electrochemical cells, and in particular to a spinel material, a proton ceramic electrochemical cell and a preparation method thereof. Background Art
[0002] Ethylene (C 2 H 4 ) is one of the key raw materials for producing various polymers and high value-added chemical products in the chemical industry. Traditionally, ethylene is produced through ethane (C 2 H 6 ) is obtained by high-temperature thermal cracking of ethane, which is energy-intensive and accompanied by large amounts of carbon dioxide emissions. Recently, ethane oxidative dehydrogenation to ethylene has attracted the most attention because, compared with traditional steam cracking, ethane oxidative dehydrogenation can react spontaneously without high temperatures and fuel consumption. However, in the ethane oxidative dehydrogenation process, ethane may be deeply oxidized to hydrocarbons instead of ethylene. In contrast, the use of non-oxidative ethane dehydrogenation (EDH) processes can avoid most of the problems associated with oxidative dehydrogenation. Moreover, the non-oxidative ethane dehydrogenation method is applicable to the conversion of natural gas containing ethane, such as combustion gas, shale gas field gas, and refinery waste gas in areas with harsh geographical conditions. Protonic ceramic electrochemical cells (PCECs) can directly convert chemical fuels into electrical energy in fuel cell mode, and can generate chemical value-added products by electrolyzing water or light alkanes (such as methane, ethane, and propane) in electrolysis mode. It is a clean, environmentally friendly and efficient energy conversion / storage device. PCECs can operate at relatively low temperatures due to the high proton conductivity and low proton migration energy barrier of the proton conductor electrolyte. Unlike conventional oxygen ion ceramic electrochemical cells, PCEC can avoid most of the problems such as poor stability, difficult sealing and high cost. For electrocatalytic non-oxidative direct dehydrogenation of ethane, lower operating temperature can avoid some related problems, including C 2 H 6 Thermal cracking and C 2 H 4 Low selectivity. As the operating temperature of PCEC decreases, the slow electrode reaction kinetics of oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and non-oxidative ethane dehydrogenation (EDH) seriously affect the electrochemical performance of PCEC. Therefore, it is a huge challenge to develop efficient electrodes for the three reactions of oxygen reduction reaction (ORR) in fuel cell mode, oxygen evolution reaction (OER) in electrolyzer mode and non-oxidative ethane dehydrogenation.
[0003] The use of highly active and durable electrode materials, especially at low temperatures, is crucial to advance the development of PCEC. Several strategies, such as surface modification, construction of heterostructures, and cation doping, have been proposed to design electrode materials with high catalytic activity and stability for oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and ethane nonoxidative dehydrogenation reaction (EDH). It is worth noting that most of the electrode materials designed for ORR / OER / EDH are related to perovskites or perovskite-related oxides. Compared with the widely studied perovskite electrodes, spinel oxides have received less attention. Due to their good thermal compatibility with other battery components, spinel oxides are widely used as coatings for interconnects of solid oxide fuel cells. Although in recent years, researchers have achieved good electrochemical performance of spinel oxides as cathodes of solid oxide fuel cells, which is comparable to some classic perovskite-based electrodes. This shows the effectiveness of using spinel oxides as oxygen electrodes and expands the range of choices for PCEC oxygen electrodes. However, the electrocatalytic activity of these spinel electrodes for oxygen evolution reaction and ethane nonoxidative dehydrogenation has not been reported. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an efficient spinel electrode material and a preparation method thereof, as well as a reversible proton ceramic electrochemical cell that can be used for power generation and electrolysis of water / ethane to synthesize chemical value-added products. The novel spinel-based composite material provided by the present invention has good electrochemical stability and exhibits high electrocatalytic activity for oxygen reduction reaction, oxygen evolution reaction and non-oxidative dehydrogenation reaction of ethane. The reversible proton ceramic electrochemical cell provided by the present invention can be simultaneously applicable to the conversion of chemical energy and electrical energy and the conversion of ethane into ethylene by electrochemical means.
[0005] In the first aspect, the present invention provides a (Cs + The spinel material is expressed as Mn 1-x Cs x Co 2 O 4-δ ; wherein x is 0.01 to 0.15, and δ is the oxygen vacancy content. + The doped spinel material has good stability, low polarization impedance and high ORR / OER activity. Preferably, the spinel material is expressed as Mn 1-x Cs x Co 2 O 4-δ ; wherein x is 0.05~0.125, δ is the oxygen vacancy content; preferably Mn 0.9 Cs 0.1 Co 2 O 4-δ, δ is the oxygen vacancy content.
[0006] According to the present invention, Cs as an A-site dopant can effectively improve the spinel oxide MnCo 2 O 4 (MCO) oxygen vacancies and improve its conductivity, thereby improving the electrocatalytic activity, that is, Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO). 3 O 4 (CO) nanoparticles have a low melting point (about 895 o C), can optimize the interface between the electrode and the electrolyte, and also has good catalytic activity for redox reactions. The present invention designs and prepares a new spinel-based composite material Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO)-Co 3 O 4 (CO) (MCCO-CO, preferably 8:2 in mass ratio) was used as a trifunctional electrode in a protonic ceramic electrochemical cell to evaluate its electrocatalytic activity, water splitting ability, and ethylene electrochemical production ability at intermediate temperatures. A spinel-based electrode material with high catalytic activity and stability was designed and applied to PCEC, providing a new field of electrode design for reversible oxygen reduction / evolution and ethylene electrochemical production on PCEC.
[0007] In a second aspect, the present invention also provides a method for preparing the spinel material, which is characterized by comprising:
[0008] 1) According to the stoichiometric ratio, manganese acetate, cesium nitrate, cobalt nitrate and water are mixed, and a complexing agent is added to obtain a mixed solution.
[0009] 2) adding ammonia water to the mixed solution, adjusting the pH value, and heating under stirring to obtain a gel-like substance.
[0010] 3) Drying the gel-like substance at high temperature to obtain a precursor.
[0011] 4) calcining the precursor to obtain a spinel material.
[0012] Preferably, in step 1), the complexing agent is ethylenediaminetetraacetic acid and citric acid monohydrate; preferably, citric acid is added at 1.5±0.2 times the molar amount of the metal ion, and ethylenediaminetetraacetic acid is added at 1±0.2 times the molar amount of the metal ion, wherein the metal element is the sum of Mn, Cs and Co; more preferably, the molar ratio of the metal element, ethylenediaminetetraacetic acid and citric acid monohydrate is 0.9~1.1:0.9~1.1:1.4~1.6, preferably 1:1:1.5.
[0013] Preferably, in step 2), the pH value is adjusted to 7-8; and / or the heating temperature is 100-180°C; preferably, the heating temperature is 120-170°C, preferably at 150°C for 5 h.
[0014] Preferably, in step 3), the high temperature drying is performed at 250-300°C for 1.5-7 hours. Preferably, the high temperature drying is performed at 280-320°C for 2-6 hours, and preferably, the precursor is dried in a blast drying oven at 300°C for 2 hours to obtain a fluffy porous precursor.
[0015] Preferably, in step 4), the calcination temperature is 900-1000°C and the calcination time is 2-4 hours. Preferably, the calcination is performed at 950°C for 3 hours to obtain the desired electrode material powder Mn 0.9 Cs 0.1 Co 2 O 4-δ (denoted as MCCO).
[0016] In the present invention, the above preferred solution successfully optimizes the preparation process of the above spinel material by precisely controlling the ratio of the complexing agent, pH value, heating temperature and time, and calcination conditions. Using ethylenediaminetetraacetic acid and citric acid as complexing agents ensures uniform dispersion of metal ions and avoids particle aggregation, thereby generating Mn with excellent conductivity and catalytic activity. 0.9 Cs 0.1 Co 2 O 4-δ Spinel material. At the same time, by high-temperature drying and calcination at an appropriate temperature, the prepared material powder presents ideal nano-scale particles, and the high specific surface area can further improve the electrocatalytic activity of the material.
[0017] In a second aspect, the present invention provides a composite spinel material, wherein the composite spinel material comprises the above spinel material or the spinel material obtained by the above preparation method; the composite spinel material preferably further comprises a spinel oxide material, wherein the expression of the spinel oxide material is Co 3 O 4 .
[0018] In the present invention, the spinel oxide material is obtained by blending raw materials including the spinel material and the spinel oxide material. 3 O 4 Composite spinel materials that are blended in a certain mass ratio to achieve the highest electrochemical performance.
[0019] Preferably, the method for preparing the spinel oxide material comprises the following steps.
[0020] 1) Dissolve cobalt nitrate in deionized water, add ethylenediaminetetraacetic acid and citric acid monohydrate into the solution as complexing agents, wherein the molar ratio of citric acid monohydrate to ethylenediaminetetraacetic acid and metal cation is 1.5:1:1; then pour ammonia water into the solution, and adjust the pH to between 7 and 8 to obtain a mixed solution.
[0021] 2) heating the mixed solution to a gel state, and subjecting the mixed solution to high temperature treatment to obtain a precursor; and calcining the precursor to obtain a spinel oxide material (Co 3 O 4 ).
[0022] Preferably, in step 1), the molar ratio of the metal element, ethylenediaminetetraacetic acid and citric acid monohydrate is 1:1:1.5; wherein the metal element is the sum of Co.
[0023] Preferably, in step 2), the mixed solution is heated to 100-180°C.
[0024] Preferably, in step 2), the high temperature treatment is performed at a temperature of 250-300°C and for a time of 5-7 h.
[0025] Preferably, in step 2), the calcination temperature is 900-1000°C and the time is 2-4 h.
[0026] Preferably, the composite spinel material comprises Mn 0.9 Cs 0.1 Co 2 O 4-δ and Co 3 O 4 , where Mn 0.9 Cs 0.1 Co 2 O 4-δ and Co 3 O 4 The mass ratio is 7~9:3~1.
[0027] The preferred embodiment of the present invention is to prepare the composite spinel material Mn 0.9 Cs 0.1 Co 2 O4-δ and Co 3 O 4 The electrochemical properties of the material were significantly improved by compounding them in a specific mass ratio, and the comprehensive performance of the composite material was optimized.
[0028] In a third aspect, the present invention provides a reversible anode-supported proton ceramic electrochemical cell, comprising a fuel electrode, an electrolyte and an air electrode arranged in sequence, preferably further comprising a transition layer between the fuel electrode and the electrolyte; the material of the air electrode comprises the above-mentioned spinel material and / or the above-mentioned composite spinel material and / or MnCo 2 O 4 .
[0029] The reversible proton ceramic electrochemical cell provided by the present invention has good stability, electrocatalytic activity and electrochemical performance, and can be used for power generation in a fuel cell mode and for the synthesis of water and ethane chemical value-added products in an electrolysis mode.
[0030] In the present invention, the air electrode can also be expressed as air electrode & positive electrode. The same electrode has different expressions in different modes. The present invention uses & to connect to express the meaning of "and / or". For example, when electrolyzing water, the electrode is called air electrode; when electrolyzing ethane, the electrode is called positive electrode. The fuel electrode can also be expressed as anode.
[0031] Preferably, the electrolyte material comprises BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ , where δ is the oxygen vacancy content.
[0032] Preferably, the material of the fuel electrode comprises NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Among them, NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio is 5~7:3~5, preferably 6:4.
[0033] Preferably, the transition layer comprises NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Among them, NiO and BaZr 0.1 Ce 0.7 Y 0.1Yb 0.1 O 3-δ The mass ratio is 6:4.
[0034] The preferred embodiment of the present invention uses the above materials in the electrolyte, fuel electrode and transition layer and compounds them in a certain mass ratio, thereby significantly improving the overall performance of the proton ceramic electrochemical cell and showing excellent electrochemical performance and cycle stability.
[0035] In a fourth aspect, the present invention provides a method for preparing the protonic ceramic electrochemical cell, comprising the following steps.
[0036] 1) The electrolyte slurry, the transition layer slurry and the fuel electrode slurry are tape-casted, degreased after drying, and then calcined at high temperature to obtain an anode-supported half-cell.
[0037] 2) The air electrode slurry is brushed onto the electrolyte surface of the half-cell and calcined at high temperature to obtain a reversible anode-supported proton ceramic electrochemical cell.
[0038] Preferably, in step 1), the temperature of the degreasing treatment is 550-750°C; and / or, in step 1), the temperature of the high-temperature calcination is 1425-1525°C; and / or, in step 2), the temperature of the high-temperature calcination is 900-1000°C.
[0039] Preferably, the degreasing treatment is carried out at a temperature of 550-750° C. and for a time of 1.5-3.5 h.
[0040] Preferably, in step 1), the high temperature calcination is carried out at a temperature of 1425-1525° C. and for a time of 5-7 h.
[0041] Preferably, in step 1), the drying is natural drying for 22 to 25 hours.
[0042] Preferably, in step 2), the high temperature calcination is carried out at a temperature of 900-1000° C. and for a time of 5-15 min.
[0043] Preferably, the electrolyte slurry is obtained by ball milling BZCYYb1711 powder, a dispersant and anhydrous ethanol.
[0044] Preferably, the slurry of the transition layer is obtained by mixing BZCYYb1711 powder, nano nickel oxide, graphite, a dispersant, anhydrous ethanol and butyl acetate, and ball milling for 20 to 30 hours.
[0045] Preferably, the slurry of the fuel electrode is obtained by mixing BZCYYb1711, nickel oxide, graphite, a dispersant, anhydrous ethanol and butyl acetate, and ball milling for 20 to 30 hours.
[0046] Preferably, the air electrode & cathode slurry is Mn 0.9 Cs 0.1 Co 2 O 4-δ 、Co 3 O 4 The spinel oxide is blended with pine alcohol; the preferred slurry composition is 0.8 g of Mn 0.9 Cs 0.1 Co 2 O 4-δ , 0.2 g of Co 3 O 4 , 0.15~0.25 g of pineneol.
[0047] In the embodiment of the present invention, the thickness of the electrolyte layer in the NiO-BZCYYb1711 anode support half-cell is 8-10 µm, the thickness of the anode support layer is 550-650 µm, and the thickness of the Ni-BZCYYb1711 transition layer is 17-23 µm.
[0048] In a fifth aspect, the present invention also provides the use of the above-mentioned reversible anode-supported protonic ceramic electrochemical cell in power generation and electrolysis of water / ethane to synthesize chemical value-added products.
[0049] The beneficial effect of the present invention is at least that: the Cs-doped novel spinel material of the present invention is a novel spinel material in the conventional spinel oxide MnCo 2 O 4 Based on the above, element doping is performed at the A position; and with Co 3 O 4 Spinel oxide blends. Anode-supported protonic ceramic electrochemical cell air electrode & positive electrode material MnCo prepared by combustion method 2 O 4 (MCO), Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO), Mn 0.9 Cs 0.1 Co 2 O 4-δ -Co 3 O 4(MCCO-CO, mass ratio is 8:2). The composite spinel electrode of the anode-supported protonic ceramic electrochemical cell of the present invention has lower polarization impedance and higher electrocatalytic activity. The anode-supported protonic ceramic electrochemical cell prepared by the present invention: NiO-BZCYYb1711||transition layer (NiO-BZCYYb1711)||BZCYYb1711||MCCO-CO has a polarization resistance of 0.076 Ω cm at 700 ℃, 650 ℃, 600 ℃, 550 ℃ and 500 ℃, respectively. 2 , 0.176 Ω cm 2 , 0.382 Ω cm 2 , 0.984 Ω cm 2 and 2.940 Ω cm 2 , the highest power density is: 1.73 W cm -2 , 1.34 W cm -2 , 0.97 W cm -2 , 0.62 W cm -2 , and 0.28 W cm -2 When humidified air was introduced into the air electrode side, the proton ceramic electrochemical cell was operated in the electrolysis mode, and the current density was -3.93 A cm at 700 ℃, 650 ℃, 600 ℃, 550 ℃, and 500 ℃ and 1.3 V, respectively. -2 , -2.48 A cm -2 , -1.45 A cm -2 , -0.56A cm -2 , and -0.24 A cm -2 The anode-supported proton ceramic electrochemical cell of the present invention has excellent stability, oxygen ion exchange kinetics, electrocatalytic activity and electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1 The electrode material Mn provided in the embodiment of the present invention 0.9 Cs 0.1 Co 2 O 4-δ XRD pattern of (MCCO) after calcination at 950°C for 3 h.
[0052] Figure 2 The air electrode material Mn provided in the embodiment of the present invention 0.9 Cs 0.1 Co 2 O 4-δ XRD pattern of (MCCO) and anode-supported half-cell electrolyte BZCYYb1711 after co-firing at 950 °C in a high-temperature muffle furnace for 10 min.
[0053] Figure 3 The electrode material Mn provided in the embodiment of the present invention 0.9 Cs 0.1 Co 2 O 4-δ (MCCO), XRD pattern after treatment at 600 °C and 30% water for 10 h.
[0054] Figure 4 The spinel electrode material MnCo provided by the embodiment of the present invention 2 O 4 (MCO) and Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO), conductivity test graph at 300~800 °C.
[0055] Figure 5 X-ray photoelectron spectra (XPS) of the air electrode materials MCCO and MCO provided in an embodiment of the present invention, wherein the left one is Co 2p and the right one is Mn 2p.
[0056] Figure 6 O1s X-ray photoelectron spectra of MCCO (left) and MCO (right) air electrode materials provided in embodiments of the present invention.
[0057] Figure 7 This is an element distribution diagram of the spinel electrode material involved in the present invention.
[0058] Figure 8 Symmetrical battery provided by the embodiment of the present invention comprises MCCO-CO composite spinel material (a), MCCO spinel material (b), and MCO spinel material (c) as electrodes, and BZCYYb1711 as an electrolyte support in humidified air (3% H 2 O) area ratio impedance diagram.
[0059] Fig. 9 The symmetrical battery MCCO-CO provided in the embodiment of the present invention, MCCO and MCO are electrodes, BZCYYb1711 is an electrolyte support, and humidified air (3% H 2 O) electrochemical stability.
[0060] Fig.10 Infrared spectra of MCO, MCCO and MCCO-CO spinel oxides provided in the embodiments of the present invention after being treated at 600 °C in air containing 30% water vapor for 50 h.
[0061] Fig.11 When MCCO-CO (a), MCCO (b), and MCO (c) are used as air electrodes in the embodiments of the present invention, the single cell (Ni-BZCYYb1711||transition layer Ni-BZCYYb1711||BZCYYb1711||MCCO-CO / MCCO / MCO) prepared with Ni-BZCYYb1711 as the fuel electrode support is tested in the fuel cell mode (humidified hydrogen is introduced into the anode side and ambient air is introduced into the oxygen electrode side) in the range of 700-500°C.
[0062] Fig.12 When MCCO-CO (a), MCCO (b), and MCO (c) are used as air electrodes in an embodiment of the present invention, a single cell (Ni- BZCYYb1711|| transition layer Ni- BZCYYb1711|| BZCYYb1711|| MCCO-CO / MCCO / MCO) prepared with Ni-BZCYYb1711 as the fuel electrode support is tested in the electrolysis mode (humidified hydrogen is introduced into the anode side and humidified air is introduced into the oxygen electrode side) in the range of 700 to 500 °C. The current density diagram corresponds to 1.3V.
[0063] Fig.13 Operation stability diagrams of a single cell (Ni-BZCYYb1711|| transition layer Ni-BZCYYb1711|| BZCYYb1711|| MCCO-CO / MCCO / MCO) prepared in an embodiment of the present invention with MCCO-CO as the air electrode and Ni-BZCYYb1711 as the anode support, tested at 650°C in single cell fuel cell mode (a) and electrolytic cell mode (b).
[0064] Fig.14 A single cell cycle stability diagram of a single cell (Ni-BZCYYb1711|| transition layer Ni-BZCYYb1711|| BZCYYb1711|| MCCO-CO / MCCO / MCO) prepared in an embodiment of the present invention with MCCO-CO as the air electrode and Ni-BZCYYb1711 as the fuel electrode support tested at 650°C.
[0065] Fig.15A graph showing the variation of the Faraday efficiency of a single cell with the applied current density of a single cell prepared with MCCO-CO as the air electrode and Ni-BZCYYb1711 as the anode support layer (Ni-BZCYYb1711||transition layer Ni-BZCYYb1711||BZCYYb1711|| MCCO-CO / MCCO / MCO) provided in an embodiment of the present invention.
[0066] Fig.16 A graph showing the change in hydrogen production rate versus applied current density of a single cell prepared with MCCO-CO as the air electrode and Ni-BZCYYb1711 as the anode support layer provided in an embodiment of the present invention.
[0067] Fig.17 The relationship between current density and voltage in a single cell prepared by using MCO, MCCO and MCCO-CO as positive electrodes and Ni-BZCYYb1711 as an anode support layer for electrochemical ethane non-oxidative dehydrogenation process.
[0068] Fig.18 Electrochemical impedance spectrum of a single cell prepared with MCO, MCCO and MCCO-CO as positive electrodes and Ni-BZCYYb1711 as an anode support layer during the electrochemical non-oxidative dehydrogenation of ethane provided in an embodiment of the present invention.
[0069] Fig.19 The single cell prepared by using MCO, MCCO and MCCO-CO as the positive electrode and Ni-BZCYYb1711 as the anode support layer provided in the embodiment of the present invention is used to improve the electrochemical stability of the electrochemical ethane non-oxidative dehydrogenation process.
[0070] Fig. 20 The single cell prepared by using MCO, MCCO and MCCO-CO as the positive electrode and Ni-BZCYYb1711 as the anode support layer provided in the embodiment of the present invention is used for the ethane conversion rate and ethylene selectivity in the electrochemical ethane non-oxidative dehydrogenation process.
[0071] Fig.21 A single cell prepared with MCO, MCCO and MCCO-CO as the positive electrode and Ni-BZCYYb1711 as the anode support layer provided in an embodiment of the present invention is used for the hydrogen production rate (a) and the corresponding Faraday efficiency (b) on the negative electrode side in the electrochemical non-oxidative dehydrogenation of ethane. DETAILED DESCRIPTION
[0072] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products or can be prepared by known methods. If no specific techniques or conditions are specified in the examples, they are all conventional methods or the techniques or conditions described in the literature in this field, or according to the product instructions. If the manufacturers of the reagents and instruments are not specified, they are all conventional products that can be purchased through regular channels.
[0074] The present invention relates to a metal cation Cs + Preparation and characterization of doped air electrode & cathode materials, the composition of the air electrode & cathode materials is Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO). By using spinel material MnCo 2 O 4 The Cs ion doping at the A site can improve the electrocatalytic activity and stability of the oxygen reduction / evolution reaction and the non-oxidative dehydrogenation of ethane in the anode-supported proton ceramic electrochemical cell. 0.9 Cs 0.1 Co 2 O 4-δ (MCCO) and Co 3 O 4 Physical mixture of spinel oxides, Mn 0.9 Cs 0.1 Co 2 O 4-δ The catalytic activity of the (MCCO) electrode can be further improved. At 700 °C, the single cell with the composition of Ni-BZCYYb1711|transition layer Ni-BZCYYb1711|BZCYYb1711|MCCO-CO has a maximum output power of 1.73 W cm in fuel cell mode. -2 , and the polarization resistance of the battery is only 0.038 Ω cm 2 When air containing 3% water vapor was introduced into the air electrode side, a current of -3.93 A cm was obtained at 700 °C and 1.3 V. -2 The current density of MnCo can be significantly reduced by doping with Cs. 2 O 4The polarization impedance of the air electrode is reduced and its electrocatalytic activity is improved. 0.9 Cs 0.1 Co 2 O 4-δ (MCCO) and Co 3 O 4 The composite spinel electrode composed of spinel oxide in a mass ratio of 8:2 showed the highest electrochemical performance.
[0075] In addition, there are relatively few studies on the cycle stability of proton ceramic electrochemical cells supported by medium and low temperature anodes, and there are very few methods for characterizing the stability of proton ceramic electrochemical cells. In order to characterize the cycle stability of the proton ceramic electrochemical cell involved in the present invention, the present invention also provides a characterization test method. The main steps are: brushing the electrode material on the electrolyte membrane of the anode-supported proton ceramic electrochemical cell, passing hydrogen containing 3% water vapor on the anode side, and passing air containing 3% water vapor on the air electrode side. The cycle stability test of the single cell is carried out, that is, by applying ±0.5 A cm -2 The anode-supported protonic ceramic electrochemical cell was operated alternately in fuel cell mode and electrolyzer mode with a current of 100 Ω, thereby evaluating the electrochemical stability of the electrode.
[0076] In the following examples: Comparative sample MCO, whose composition is MnCo 2 O 4 , and its preparation process is the same as that in the embodiment.
[0077] Example 1
[0078] This embodiment provides an anode-supported proton ceramic electrochemical cell air electrode material MnCo 2 O 4 The specific steps of its preparation are as follows: 1) According to the stoichiometric ratio, manganese acetate and cobalt nitrate are mixed in the ratio of MnCo 2 O 4 The stoichiometric ratio of (MCO) was added to the deionized water solution in sequence. Subsequently, citric acid was added at 1.5 times the molar amount of the metal ions, and ethylenediaminetetraacetic acid was added at 1 times the molar amount of the metal ions.
[0079] 2) After adding the complexing agent to the solution containing the metal ions, add ammonia water, adjust the pH value to 7-8, and then heat and stir under magnetic stirring until the water is evaporated to obtain a gel-like substance.
[0080] 3) The gel-like substance is placed in a forced air drying oven and dried at 300°C for 2 hours to obtain a fluffy porous precursor.
[0081] 4) The precursor is placed in a high-temperature muffle furnace and calcined at 950 °C for 3 hours to obtain the desired electrode material powder MnCo 2 O 4 (Recorded as MCO).
[0082] Example 2
[0083] This embodiment provides an anode-supported proton ceramic electrochemical cell air electrode material Mn 0.9 Cs 0.1 Co 2 O 4-δ The preparation method, and the specific steps of its preparation are as follows.
[0084] 1) According to the stoichiometric ratio, manganese acetate, cesium nitrate and cobalt nitrate are added in the ratio of Mn 0.9 Cs 0.1 Co 2 O 4-δ The stoichiometric ratio of (MCCO) was added to the deionized water solution in sequence. Subsequently, citric acid was added at 1.5 times the molar amount of metal ions, and ethylenediaminetetraacetic acid was added at 1 times the molar amount of metal ions.
[0085] 2) After adding the complexing agent to the solution containing the metal ions, add ammonia water, adjust the pH value to 7-8, and then heat and stir under magnetic stirring until the water is evaporated to obtain a gel-like substance.
[0086] 3) The gel-like substance is placed in a forced air drying oven and dried at 300°C for 2 hours to obtain a fluffy porous precursor.
[0087] 4) The precursor is placed in a high-temperature muffle furnace and calcined at 950 °C for 3 hours to obtain the desired electrode material powder Mn 0.9 Cs 0.1 Co 2 O 4-δ (denoted as MCCO).
[0088] Example 3
[0089] This embodiment provides an anode-supported proton ceramic electrochemical battery electrode material Co 3 O 4 The preparation method, and the specific steps of its preparation are as follows.
[0090] 1) Cobalt nitrate, according to Co 3 O 4 The stoichiometric ratio of (CO) was added to the deionized water solution. Subsequently, citric acid was added at 1.5 times the molar amount of the metal ions, and ethylenediaminetetraacetic acid was added at 1 times the molar amount of the metal ions.
[0091] 2) After adding the complexing agent to the solution containing the metal ions, add ammonia water, adjust the pH value to 7-8, and then heat and stir under magnetic stirring until the water is evaporated to obtain a gel-like substance.
[0092] 3) The gel-like substance is placed in a forced air drying oven and dried at 300°C for 2 hours to obtain a fluffy porous precursor.
[0093] 4) The precursor was placed in a high-temperature muffle furnace and calcined at 950 °C for 3 hours to obtain the desired electrode material powder Co 3 O 4 (denoted as CO).
[0094] Example 4
[0095] This embodiment provides a MnCo 2 O 4 (MCO) or Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO) or Mn 0.9 Cs 0.1 Co 2 O 4-δ -Co 3 O 4 A reversible anode-supported protonic ceramic electrochemical cell of Ni-BZCYYb1711|transition layer Ni-BZCYYb1711|BZCYYb1711|MCO / MCCO / MCCO-CO is prepared using a composite spinel oxide (MCCO-CO, mass ratio is 8:2) as the air electrode of the battery, which specifically includes the following steps.
[0096] (1) Preparation of electrolyte layer slurry: 6 g BZCYYb1711 powder, 0.2 g fish oil dispersant, 1.6 g anhydrous ethanol, and 1.6 g butyl acetate were uniformly mixed to obtain BZCYYb1711 electrolyte layer slurry; Preparation of transition layer slurry: 2.4 g BZCYYb1711 powder, 3.6 g nano nickel oxide, 0.6 g graphite, 0.2 g fish oil dispersant, 1.5 g anhydrous ethanol, and 1.5 g butyl acetate were uniformly mixed to obtain Ni-BZCYYb1711 transition layer slurry; Preparation of anode support layer slurry: 20 g BZCYYb1711, 30 g nickel oxide, 3.0 g graphite, 2.0 g fish oil dispersant, 6.0 g anhydrous ethanol, and 6.0 g butyl acetate were uniformly mixed to obtain anode slurry; the above slurries were placed on a drum ball mill and ball milled for 20-30 min. h.
[0097] (2) The electrolyte slurry, transition layer slurry and anode slurry after ball milling and blending were cast on a polyethylene terephthalate release film in sequence, and then the co-cast electrolyte layer-transition layer-anode support layer film was placed in the air to dry naturally for 16 h, and then cut into several thin sheets with a diameter of 15 mm using a molding mold with a diameter of 15 mm, and placed in a muffle furnace for degreasing treatment at 600 °C for 2 h; finally, the degreased thin sheets were placed in a high-temperature muffle furnace and calcined at 1450 °C for 5 h to obtain the desired anode-supported half-cell; wherein the prepared anode-supported half-cell includes a BZCYYb1711 electrolyte layer (thickness of 6~8 µm), a Ni-BZCYYb1711 transition layer (thickness of 30~40 µm) and a Ni-BZCYYb1711 anode support layer (thickness of 500~600 µm).
[0098] (3) Weigh 1 g of the air electrode powder MnCo prepared in Example 1. 2 O 4 The mixture was uniformly mixed with 0.3 g of pinene alcohol and 0.04 g of ethyl cellulose for 1.5 h to obtain the desired spinel electrode slurry.
[0099] (4) Weigh 1 g of the air electrode powder Mn prepared in Example 2. 0.9 Cs 0.1 Co 2 O 4-δ The mixture was uniformly mixed with 0.3 g of pinene alcohol and 0.04 g of ethyl cellulose for 1.5 h to obtain the desired spinel electrode slurry.
[0100] (5) Weigh 0.8 g of the air electrode powder prepared in Example 1 and 0.2 g of the electrode powder prepared in Example 4, and mix them evenly with 0.3 g of pine alcohol and 0.04 g of ethyl cellulose for 1.5 h to obtain the desired spinel electrode slurry.
[0101] (6) The prepared air electrode slurry was brushed onto the electrolyte membrane of the half-cell and then placed in an oven at 70 °C. After the cathode slurry was dried, the assembled full cell was calcined at 950 °C in a high-temperature muffle furnace for 10 min for electrochemical performance testing in fuel cells, electrolyzers, and ethane electrolysis modes.
[0102] The characterization results of the above embodiments of the present invention are as follows.
[0103] 1. XRD characterization
[0104] Figure 1 Mn 0.9 Cs 0.1 Co 2 O 4-δThe XRD refinement of the (MCCO) powder after calcination at 950 °C for 3 h shows that the synthesized MCCO shows a single spinel phase structure. At the same time, the XRD refinement results show that the space group configuration of the synthesized MCCO is Fd-3m, and its lattice parameters are a = b = c = 8.2492 Å (refinement parameters: GOF = 1.03).
[0105] Figure 2 The chemical compatibility of the synthesized air electrode material MCCO and the electrolyte membrane of the proton ceramic electrochemical cell. As can be seen from the figure, after MCCO and the BZCYYb1711 electrolyte membrane were calcined at 950 ° C in a high-temperature muffle furnace for 10 min, there was no chemical reaction between the powder and the electrolyte membrane, indicating that the MCCO spinel material has good chemical compatibility with the BZCYYb1711 electrolyte membrane.
[0106] Figure 3 Mn 0.9 Cs 0.1 Co 2 O 4-δ XRD image of (MCCO) powder after treatment at 600℃ in air containing 30% water vapor for 10h. The main peak of the XRD image of the treated MCCO is obviously shifted to a lower angle, which may be due to the expansion of the lattice caused by the entry of water vapor into the lattice.
[0107] Figure 4 MnCo 2 O 4 (MCO) and Mn 0.9 Cs 0.1 Co 2 O 4-δ (MCCO) spinel material is 300~800 o Conductivity test at 40 °C. It can be seen from the figure that the conductivity of MCO and MCCO powder increases with the increase of temperature, and MCCO exhibits higher conductivity. Higher conductivity is more conducive to charge transfer and thus accelerates the reaction rate.
[0108] 2. X-ray Photoelectron Spectroscopy (XPS) Characterization
[0109] According to the fitting data, after Cs partially replaces the A-position Mn element in MCO, the proportion of high-valence states of Co and Mn is further increased in order to maintain the electrical neutrality of the material. Figure 5 (Left) shows that Co in MCO 4+ The content of Co in MCCO is 31.6%. 4+ The content of Mn increased to 39.9%. The Mn element also showed a similar trend, such as Figure 5 (right) As shown. In MCO, Mn 3+and Mn 4+ The contents of Cs in MCO are 36.6% and 25.3%, respectively, while in MCCO, these contents increase to 41.5% and 29.3%, respectively. XPS results show that the incorporation of Cs in MCO leads to an increase in the content of high-valent cations of Co and Mn.
[0110] The corresponding O 1s XPS fitting data of MCCO and MCO are as follows: Figure 6 The O1s peaks of MCCO (left) and MCO (right) can be divided into four subordinate peaks, including lattice oxygen (O lat ), high oxidizing oxygen (O - / O 2 2- ), adsorbed oxygen (O ads ) and oxygen in the hydroxyl environment (OH - ). Among them, O - / O 2 2 and O lat The ratio of MCCO to MCO reflects the content of oxygen vacancies, and the ratios of MCCO and MCO are 0.61 and 0.41, respectively. - / O 2 2- The proportion of is generally considered to play a key role in the ORR process.
[0111] 3. Element distribution diagram
[0112] Figure 7 It is a new type of spinel oxide Mn prepared 0.9 Cs 0.1 Co 2 O 4-δ Element distribution diagram of (MCCO). It can be seen from the figure that Mn, Cs, Co and O elements are evenly distributed, and no aggregation and precipitation of elements are observed, indicating that Cs successfully enters MnCo 2 O 4 (MCO) in the crystal lattice of spinel oxide.
[0113] 4. Electrochemical impedance and stability study
[0114] For the first time, we measured the symmetric cell supported by BZCYYb1711 in humid air (3% H 2 O) in the area specific resistance, and the electrocatalytic activities of MCO, MCCO and MCCO-CO air electrodes were studied. Figure 8 As shown in (a), at 700, 650, 600, 550 and 500 °C, the surface resistivity of the MCCO-CO air electrode reaches 0.076, 0.176, 0.382, 0.984 and 2.940 Ω cm, respectively.2 . Figure 8 (b) shows the electrocatalytic activity of the MCCO air electrode. Under the same test conditions, the surface resistivity of the MCCO air electrode reaches 0.119, 0.231, 0.572, 1.588, and 4.382 Ω cm at 700, 650, 600, 550, and 500 °C, respectively. 2 . Figure 8 c is the surface resistivity of the MCO air electrode, which is 0.157, 0.295, 0.869, 2.649 and 6.153 Ω cm at 700, 650, 600, 550 and 500 °C, respectively. 2 Compared with MCO and MCCO air electrodes, the MCCO-CO air electrode exhibits higher electrocatalytic activity.
[0115] Fig. 9 MCO, MCCO and MCCO-CO in humid air (3% H 2 When exposed to humid air, the surface specific resistance values of the air electrodes with MCO, MCCO, and MCCO-CO all showed good stability and electrocatalytic activity.
[0116] 7. Fourier transform infrared spectroscopy (FTIR) characterization
[0117] Fig.10 The Fourier transform infrared spectra of MCO, MCCO, and MCCO-CO spinel oxides treated in humid air containing 30% water vapor at 600°C for 50 h are shown. FTIR measurements can identify the hydroxyl signal value in the oxide, and its characteristic peak appears at 3400~3800 cm -1 The test results show that the hydroxyl peak intensity of MCCO-CO treated with 30% water vapor is slightly higher than that of MCCO and MCO oxide, indicating that MCCO-CO exhibits better hydration behavior.
[0118] 8. Electrochemical performance test
[0119] The battery prepared in Example 4 was used to perform an electrochemical power density test in a fuel cell mode (FC mode) and a current density test in an electrolysis mode (EC mode). Fig.11 The full cell consisting of MCCO-CO, MCCO and MCO as air electrodes involved in the present invention was tested under the fuel cell mode, with humidified hydrogen introduced on the anode side and the atmosphere on the air electrode side being air. Fig.11 (a) The power density of the MCCO-CO single cell tested in the range of 700-500 °C is 1.73 W cm -2 ,1.34 W cm -2, 0.97 W cm -2 , 0.62 W cm -2 , and 0.28 W cm -2 . Fig.11 (b) The power density of the MCCO single cell tested in the range of 700-500 °C is 1.19 W cm -2 ,0.87 W cm -2 , 0.58 W cm -2 , 0.37 W cm -2 , and 0.20 W cm -2 . Fig.11 c is the power density of the MCO single cell tested in the range of 700-500 °C, which is 0.86 W cm -2 ,0.52 W cm -2 , 0.31 W cm -2 , 0.20 W cm -2 , and 0.11 W cm -2 .
[0120] Fig.12 The IV curve diagram of the single cell (Ni-BZCYYb1711||BZCYYb1711||PBCsC) prepared by using MCCO-CO, MCCO and MCO as air electrodes and Ni-BZCYYb1711 as fuel electrode support and tested in EC mode (humidified hydrogen is introduced into the anode side and humidified air is introduced into the oxygen electrode side) in the range of 700-500°C. Fig.12 (a) The electrolysis performance of the MCCO-CO air electrode is shown in Figure 2. The current density is -3.93 A cm at 1.3 V at 700, 650, 600, 550, and 500 °C, respectively. -2 , -2.48 A cm -2 , -1.45 A cm -2 , -0.56 A cm -2 , and -0.24 A cm -2 . Fig.12 (b) The electrolysis performance of the MCCO air electrode is shown in Figure 2. The current density is −2.56 A cm at 1.3 V at 700, 650, 600, 550, and 500 °C, respectively. -2 , -1.51 A cm -2 , -0.83 A cm -2 , -0.37 A cm -2 , and -0.14 A cm -2 . Fig.12c is the electrolysis performance of the MCO air electrode. The current density is -1.77 A cm at 1.3 V at 700, 650, 600, 550 and 500 °C, respectively. -2 , -1.03 A cm -2 , -0.53 A cm -2 , -0.27 A cm -2 , and -0.12 A cm -2 The electrolytic cell with MCCO-CO air electrode also showed better electrolytic performance.
[0121] 9. Single cell stability and cycle test
[0122] Fig.13 (a) MCCO-CO air electrode at 650 °C with a current density of 0.5 A cm -2 , the long-term stability of the cell running in fuel cell mode for 223 hours. In addition, due to the presence of humid air in the air electrode chamber of the proton ceramic electrochemical cell, the air electrode's tolerance to steam is critical to the stability of the cell. Fig.13 (b) shows the full cell of MCCO-CO air electrode in humid air (3% H 2 O) as an oxidant in the electrolysis mode, showing good stability at -0.5 A cm -2 and 650 °C for 209 h. -2 At 650 °C, a cyclic test of FC and EC dual-mode switching was carried out every 2 h ( Fig.14 ). The cell with MCCO-CO air electrode exhibits good stability during 208 h of reversible operation.
[0123] 10. Faradaic efficiency and hydrogen production rate test
[0124] The Faradaic efficiency is crucial for hydrogen production in the electrochemical process of proton conductor solid oxide fuels in the reversible mode and is defined as the actual amount of H produced. 2 The rate (measured by gas chromatography) and the theoretical generation of H 2 The ratio of the rates (calculated from the impressed current). Fig.15 and Fig.16 The Faradaic efficiency and hydrogen production rate at different current densities and 600 °C humid air (steam concentration of 30%) are shown. -2 When different current densities are applied, the Faradaic efficiency decreases from 83.4% to 67.2% and 53.6% ( Fig.15). In addition, at -0.5, -0.75 and -1.0 A cm -2 At the current density, the corresponding H 2 The spawn rate increased from 2.91 to 3.51 and 3.73 as Fig.16 shown.
[0125] 10. Electrochemical ethane non-oxidative dehydrogenation test
[0126] Fig.17 The results show that MCO, MCCO and MCCO-CO are used as the positive electrode of a single cell at 700 o The relationship between current density and voltage on a single cell during non-oxidative dehydrogenation of ethane at 240 °C. Compared with MCO and MCCO, the MCCO-CO cathode exhibits a higher current density, and the increased current density is beneficial to accelerate the non-oxidative dehydrogenation reaction of ethane. Fig.18 The present invention relates to an electrochemical impedance spectrum of a single cell with MCO, MCCO and MCCO-CO as positive electrodes during the electrochemical ethane non-oxidative dehydrogenation process. The decrease in polarization resistance is related to the difference in positive electrode and potential, and increasing the applied voltage can enhance the reaction kinetics of ethane non-oxidative dehydrogenation. Fig.19 The present invention relates to single cells with MCO, MCCO and MCCO-CO as positive electrodes for electrochemical ethane non-oxidative dehydrogenation process. Under different voltages, these single cells all show good electrochemical stability. Fig. 20 The single cell prepared by using MCO, MCCO and MCCO-CO as positive electrodes and Ni-BZCYYb1711 as anode support layer is used for the ethane conversion rate and ethylene selectivity in the electrochemical ethane non-oxidative dehydrogenation process. Among them, the ethane conversion rate and ethylene selectivity of the MCCO-CO single cell are 40.3% and 94%, which are higher than those of the MCCO and MCO single cells. Fig.21 The single cell prepared by using MCO, MCCO and MCCO-CO as the positive electrode and Ni-BZCYYb1711 as the anode support layer for the electrochemical non-oxidative dehydrogenation of ethane (a) and the corresponding Faraday efficiency (b). When the applied potential increases from 1.3 V to 1.5 V, the corresponding H 2 The production rate is from 2.8 mL min -1 cm -2 Increased to 4.65 mL / min -1 cm -2 , FE dropped from 97% to 80%.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A spinel material, characterized in that: The spinel material is expressed as Mn 1-x Cs x Co2O 4-δ ; where x is 0.01~0.15 and δ is the oxygen vacancy content.
2. The spinel material according to claim 1, characterized in that The expression is Mn 1-x Cs x Co2O 4-δ ; wherein x is 0.05~0.125, δ is the oxygen vacancy content; preferably Mn 0.9 Cs 0.1 Co2O 4-δ , δ is the oxygen vacancy content.
3. The method for preparing the spinel material according to claim 1 or 2, characterized in that: include: 1) mixing manganese acetate, cesium nitrate, cobalt nitrate and water according to a stoichiometric ratio, and adding a complexing agent to obtain a mixed solution; 2) adding aqueous ammonia to the mixed solution, adjusting the pH value, and heating under stirring to obtain a gel-like substance; 3) drying the gel-like substance at high temperature to obtain a precursor; 4) calcining the precursor to obtain a spinel material.
4. The method for preparing the spinel material according to claim 3, characterized in that: In step 1), the complexing agent is ethylenediaminetetraacetic acid and citric acid monohydrate; and / or, in step 2), adjusting the pH value to 7-8; and / or, the heating temperature is 100-180°C; And / or, in step 3), the high temperature drying temperature is 250-300°C; And / or, in step 4), the calcination temperature is 900-1000°C and the time is 2-4 h.
5. A composite spinel material, characterized in that: The composite spinel material comprises the spinel material described in claim 1 or 2 or the spinel material obtained by the preparation method described in claim 3 or 4; the composite spinel material preferably also contains a spinel oxide material, and the expression of the spinel oxide material is Co3O4.
6. The composite spinel material according to claim 5, characterized in that: The composite spinel material comprises Mn 0.9 Cs 0.1 Co2O 4-δ and Co3O4, among which Mn 0.9 Cs 0.1 Co2O 4-δ The mass ratio of Co3O4 is 7~9:3~1.
7. A reversible anode-supported proton ceramic electrochemical cell, characterized in that: It comprises a fuel electrode, an electrolyte and an air electrode arranged in sequence, and preferably also comprises a transition layer located between the fuel electrode and the electrolyte; the material of the air electrode comprises the spinel material described in claim 1 or 2 and / or the composite spinel material and / or MnCo2O4 described in claim 5 or 6.
8. The protonic ceramic electrochemical cell according to claim 7, characterized in that: The electrolyte material includes BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ , wherein δ is the oxygen vacancy content; and / or, the material of the fuel electrode comprises NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Among them, NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio of NiO and BaZr is 5-7:3-5; and / or, the transition layer comprises NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Among them, NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio is 5~7:3~5.
9. The method for preparing the proton ceramic electrochemical cell according to claim 7 or 8, characterized in that: The following steps are involved: 1) The electrolyte slurry, the transition layer slurry and the fuel electrode slurry are subjected to tape casting, degreased after drying, and then calcined at high temperature to obtain an anode-supported half-cell; 2) The air electrode slurry is brushed onto the electrolyte surface of the half-cell and calcined at high temperature to obtain a reversible anode-supported proton ceramic electrochemical cell.
10. The method for preparing a proton ceramic electrochemical cell according to claim 9, characterized in that: In step 1), the temperature of the degreasing treatment is 550-750°C; and / or, in step 1), the temperature of the high-temperature calcination is 1425-1525°C; and / or, in step 2), the temperature of the high-temperature calcination is 900-1000°C.
